A comparison of knee joint laxity among male and female collegiate soccer players and non-athletes - Medrano, D.; Smith, D. (Sports Biomechanics, 2003)
Female athletes are at least twice as likely to sustain an anterior cruciate ligament injury than male athletes. The underlying cause of ACL injury is multifactorial. However, several researchers have identified knee joint laxity as a possible contributing factor. The purpose of this study was to provide a comparison of knee joint laxity between male and female collegiate soccer players and male and female non-athletes. Thirty-nine (19 male, 20 female) apparently healthy collegiate athletes form the University of Texas at El Paso's 2001-2002 women's intercollegiate soccer team and men's club soccer team, and forty (20 male, 20 female) non-athletic students volunteered to participate. All participants were tested bilaterally using the KT-1000 MEDmetric knee joint ligament arthrometer. Three tests were used to determine anterior laxity: passive displacement, active displacement, and the Lachman test. The mean passive displacement, mean active displacement, and Lachman (only for the left leg) were significantly lower for the athletic group than for the non-athletic group. There were no significant differences found between males and females for the passive and active drawer tests. However, females had significantly more laxity than males in the Lachman test. These findings suggest that strength and conditioning may play a more significant role in knee joint laxity than the sex of the individual.